Global incidence and mortality of idiopathic pulmonary fibrosis: a systematic review - Hutchinson, John P.; Fogarty, Andrew W.; Hubbard, Richard B.; McKeever, Tricia M. (European Respiratory Society, 2015)
Introduction: As idiopathic pulmonary fibrosis emerges as an important public health problem, there is a need to coordinate data on incidence and mortality globally. This study aims to systematically assess all available studies to investigate the global burden of disease.